The global cost of epilepsy: A systematic review and extrapolation. Issue 4 (23rd February 2022) - Begley, Charles; Wagner, Ryan G.; Abraham, Annette; Beghi, Ettore; Newton, Charles; Kwon, Churl‐Su; Labiner, David; Winkler, Andrea S.
Abstract: Objective: Global action for epilepsy requires information on the cost of epilepsy, which is currently unknown for most countries and regions of the world. To address this knowledge gap, the International League Against Epilepsy Commission on Epidemiology formed the Global Cost of Epilepsy Task Force. Methods: We completed a systematic search of the epilepsy cost‐of‐illness literature and identified studies that provided a comprehensive set of direct health care and/or indirect costs, followed standard methods of case identification and cost estimation, and used data on a representative population or subpopulation of people with epilepsy. Country‐specific costs per person with epilepsy were extracted and adjusted to generate an average cost per person in 2019 US dollars. For countries with no cost data, estimates were imputed based on average costs per person of similar income countries with data. Per person costs for each country were then applied to data on the prevalence of epilepsy from the Global Burden of Disease collaboration adjusted for the treatment gap. Results: One hundred one cost‐of‐illness studies were included in the direct health care cost database, 74 from North America or Western Europe. Thirteen studies were used in the indirect cost database, eight from North America or Western Europe. The average annual cost per person with epilepsy in 2019 ranged from 204 in low‐income countries to 11 432 in high‐income countries based on this highly skewed database. The total cost of epilepsy, applying per person costs to the estimated 52.51 million people in the world with epilepsy and adjusting for the treatment gap, was 119.27 billion. Significance: Based on a summary and extrapolations of this limited database, the global cost of epilepsy is substantial and highly concentrated in countries with well‐developed health care systems, higher wages and income, limited treatment gaps, and a relatively small percentage of the epilepsy population.